2022
DOI: 10.1002/rmb2.12463
|View full text |Cite
|
Sign up to set email alerts
|

The effects of differences in trophectoderm biopsy techniques and the number of cells collected for biopsy on next‐generation sequencing results

Abstract: Purpose To examine how differences in trophectoderm biopsy techniques affect the frequency of mosaic embryos and sequencing results. Methods We examined differences in next‐generation sequencing (NGS) analysis results among operators or according to biopsy technique. Additionally, we determined the cut‐off for the number of collected cells to predict the occurrence of mosaicism. We collected cells according to the cut‐off value and examined whether there was a differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…1), while even modest differences affected detection of mosaicisms (Fig. 3), and concordance studies such as those with blastocyst rebiopsy samples [37][38][39][40] could benefit from normalization of noise, as in this study. However, currently there are no guidelines how to deal with technical noise in mosaicism studies 2 .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…1), while even modest differences affected detection of mosaicisms (Fig. 3), and concordance studies such as those with blastocyst rebiopsy samples [37][38][39][40] could benefit from normalization of noise, as in this study. However, currently there are no guidelines how to deal with technical noise in mosaicism studies 2 .…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, biopsy techniques significantly affect the pregnancy outcome according to data from different fertility centers 3,[48][49][50] and sub-optimal biopsy techniques could cause damage to embryos 2,[48][49][50] . Blastocysts that are not particularly high in quality are especially susceptible to damage 40 and there is no standardization of blastocyst biopsy procedures between the centers 20 , again increasing variability. There is no standardized system to interpret and report PGT-A data either 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Collecting an insu cient number of cells might result in inaccurate analysis; in contrast, collecting more cells than required, as when using the icking method, can cause signi cant damage to the blastocyst. We previously reported that the number of cells needed to be collected for adequate analysis while not damaging the embryo was 5 [7]. Furthermore, NGS analysis was stable at our institute, irrespective of which technician performed the experiment.…”
Section: Discussionmentioning
confidence: 88%
“…A biopsy is generally performed by aspirating the required amount of TE cells and cutting them by laser irradiation (pulling method) or rubbing them into a holding pipette ( icking method). In this study, we used the pulling method [9] as previous studies indicated that the icking method collects more TE cells than those obtained by the pulling method [7]. The pulling method irradiates the targeted area with a laser, making cell collection easy to control and, thus, ensuring a more accurate collection of the intended number of cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation